2007
DOI: 10.1108/02635570710740670
|View full text |Cite
|
Sign up to set email alerts
|

A value chain perspective of internet practices, e‐readiness and organizational performance

Abstract: Purpose -The internet has become a ubiquitous technology for business and it possesses the potential to make the concept of value chain into a more attainable reality. The purpose of this paper is to conjecture that the way the internet is utilized and the extent to which the internet impacts business performance vary from country to country. The paper aims to compare two countries regarding the pattern of internet utilization, the impact of the internet on organizational performance, and the readiness for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Much research, instead, primarily focuses on the CRM technology solutions pursued by large organizations, which tend to involve complex software applications and information systems [85,145]. Such advanced CRM applications, however, are not likely to be relevant to the unique needs of SMEs [72,97]. This is so for several reasons.…”
Section: Literature Background Ecrm and Smesmentioning
confidence: 97%
See 1 more Smart Citation
“…Much research, instead, primarily focuses on the CRM technology solutions pursued by large organizations, which tend to involve complex software applications and information systems [85,145]. Such advanced CRM applications, however, are not likely to be relevant to the unique needs of SMEs [72,97]. This is so for several reasons.…”
Section: Literature Background Ecrm and Smesmentioning
confidence: 97%
“…Prior research, however, has shown that SMEs lag behind larger organizations in their adoption of CRM software applications due to financial, managerial, and strategic concerns [72,84,91,140]. In fact, research has shown that the majority of SMEs do not use dedicated CRM applications to support their customer relationships [32,73].…”
mentioning
confidence: 96%
“…Despite signifi cant technological advances and increasing organizational investment in these technologies, the problem of underutilized systems plagues businesses (Venkatesh, 2000). Today, management's embrace of new technology is a crucial indicator of how successfully ICT will be diffused throughout an organization to improve business performance (Koh, Nam, Prybutok, & Lee, 2007). The Primary contributions of ICT to performance can be measured at the operational level within a fi rm (Barua et al, 1995).…”
Section: Theory and Hypothesesmentioning
confidence: 99%